HUBUNGAN ANTARA KEPEMIMPINAN, MOTIVASI KERJA, IKLIM ORGANISASI DAN KINERJA KARYAWAN PADA SEKRETARIAT DAERAH KOTA PALEMBANG - Zet Abdullah (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
The research aims to determine the relationship between leadership (X1), motivation (X2), organizational climate (X3) and employee performance (Y) at the Regional secretariat of Palembang City. The sample in this study was 102 respondents. The sample-sampling technique in the study was carried out with a sample random sampling technique. Data collection method using questionnaire. The Data obtained is then processed by using the SPSS tool. The analysis techniques used include validity tests, reusability tests, the correlation test of Kendall's tau, hypothesis tests through partial correlation tests, double correlation, Ttest and Ftest tests. Based on the calculation results of the double correlation statistics of 1.7615 shows the relationship between the variable leadership, motivation, organizational climate and employee performance is very strong. T test result proves that the leadership variables are unrelated and significant with the employee's performance, the motivation variables are unrelated and significant with the employee's performance, and the organizational climate is unrelated and significant with the employee's performance. While the simultaneous F test results of 1.761 indicate that there is a simultaneous relationship between leadership, motivation, organizational climate and employee performance with a very strong relationship level.